Resource mobilization and linkages for curricular development - Misajon, Mervyn J. (1990)
Largely attributed to the lack of public managers with administrative capability, management crisis can be averted through an education and training program responsive to the bureaucrats' needs. Resource constraints, admittedly crippling and retrogressive to management education curriculum or program development, pose the challenge both to the administrator and the faculty to be more resourceful and innovative. The administrator and faculty can strengthen their capabilities to acquire or produce resources either by (a) pooling with external agencies in forward or backward linkages or (b) supplementing its own institutional resources by tapping local and international funding sources to finance distinct research and training projects, actively participating in the activities of government agencies at national and subnational levels as well as the nongovernmental organizations, and advertising and enhancing public relations.
Keywords: Public administration -- Study and teaching; Public administration -- Curricula (Courses of study); Public Management Education (PME)